HUMAN RIGHTS AND DATA PROTECTION IN THE DIGITAL FINANCIAL ECOSYSTEM - Hidayatulloh Hidayatulloh (JHR (Jurnal Hukum Replik), 2023)
Indonesia passed Law Number 27 of 2022 concerning the Protection of Personal Data, a notable instrument in preventing privacy and data protection rights violations. This paper analyzes the relationship between human rights and personal data protection in digital financial transactions. In the findings of this paper, privacy rights and data protection rights are human rights that are interrelated with one another. Both are essential parts of protecting human honor and dignity. In matters of personal data, leakage and theft are the leading digital security issues in financial institutions, especially banks. The community hopes that Law Number 27 of 2022 can provide protection, especially the security of digital financial transactions that continue to develop in Indonesia.Keywords: human rights, personal data protection, digital finance